2018
DOI: 10.1590/s0100-83582017350100089
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic Effect of Some Associated Weeds of Wheat on Germinability and Biomass Production of Wheat Seedlings

Abstract: Weeds associated with crops may impose their phytotoxic effects on crop plants through the release of their allelochemicals and hence seriously reduce crop productivity. The present study was conducted to investigate the allelopathic effect of water soluble phenolics of weeds associated with wheat crop (Vicia sativa, Trigonella polycerata, Lathyrus aphaca, Medicago polymorpha, Melilotus indica) on germinability and biomass production of wheat seedlings by using their water extracts at 2.5% (w/v) and 5% (w/v) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In 2018 it was observed at all locations that, after a short time period, the vetch was infested with mildew and died. Root excretions and leaching's (vanillin acid, p-coumaric acid, ferulic acid) of above-ground common vetch biomass is shown to inhibit the germination of wheat, as well as plant growth and development [66]. Their study concluded that wheat produced more root biomass than above ground biomass, due to the allelopathic substances.…”
Section: Influence Of Ifp On Maize Croppingmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2018 it was observed at all locations that, after a short time period, the vetch was infested with mildew and died. Root excretions and leaching's (vanillin acid, p-coumaric acid, ferulic acid) of above-ground common vetch biomass is shown to inhibit the germination of wheat, as well as plant growth and development [66]. Their study concluded that wheat produced more root biomass than above ground biomass, due to the allelopathic substances.…”
Section: Influence Of Ifp On Maize Croppingmentioning
confidence: 99%
“…Also, the DMY was reduced. Common vetch is a plant which leaches allelopathic substances during decomposition of its biomass [66]. In 2018 it was observed at all locations that, after a short time period, the vetch was infested with mildew and died.…”
Section: Influence Of Ifp On Maize Croppingmentioning
confidence: 99%
“…One of the major challenges to wheat growth and yield is its interspecific competition with weeds, such as black mustard (Brassica nigra (L.) Koch), for environmental resources [1][2][3][4]. The application of weedicides is considered as one of the suitable practices to control weeds' growth, but unfortunately, it comes with major concerns about food safety as well as causing environmental pollution [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…By regulating enzyme activity, protein synthesis, photosynthesis, respiration, cell division, and enlargement, among other physiological functions, they produce significant reductions in crop germination and growth, resulting in a significant drop in crop production. Allelopathic weeds, in short, are a possible hazard to crop plants and can result in financial losses 25 .…”
Section: Discussionmentioning
confidence: 99%